Cold end forming of thin-walled PVC tubes using a die. (13th September 2010) - Alves, L.M.; Martins, P.A.F.
The aim of this paper is to evaluate the applicability of tube end-forming processes, currently applied in metals, to polyvinyl chloride (PVC). The presentation is focused on four different processes (expansion, reduction, internal and external inversion) and its contents are expected to provide new fundamental level of knowledge and understanding about the mechanics of deformation and the expected modes of deformation of PVC tubes. The formability limits are defined in terms of the major operating variables with the purpose of predicting the behaviour of PVC tubes across a wide range of working conditions. The experimental findings are interpreted in the light of an innovative extension of the finite element flow formulation that is capable of modelling cold plastic deformation of pressure-sensitive materials under a non-associated flow rule. Special emphasis is placed on the analysis of load-displacement, local buckling, ductile damage and crazing. The overall results confirm that end-forming of thin-walled PVC tubes at room temperature have potential for the manufacture of custom and specific shapes.